Clinical characteristics and risk factors for 90-day overall survival among 204 adult patients with secondary hemophagocytic lymphohistiocytosis: Experience from a single-center retrospective study - Wang, Dongguang; Tong, Xiang; Liu, Sitong; Zhang, Wentao; Wang, Lian; Zhang, Shijie; Zhang, Tianli; Wang, Qian; Fan, Hong (Frontiers in Medicine, 2022)
Objectives: To describe the clinical characteristics of secondary hemophagocytic lymphohistiocytosis (HLH) among adult patients, investigate its risk factors for 90-day overall survival (OS) from diagnosis, and establish a new prognostic model applicable to adult patients with secondary HLH. Methods: We conducted a retrospective cohort study of 204 adult patients with secondary HLH, between January 2010 and December 2020. All patients met at least five HLH-2004 criteria. Clinical features, laboratory results, treatments, and clinical outcomes of the patients were reviewed. Prognostic factors associated with 90-day overall survival from diagnosis were screened using Cox proportional hazard models. Results: The most common trigger was malignancy (61.3%). Multivariate analysis showed that age, coagulopathy, levels of hemoglobin, aspartate aminotransferase (AST), lactate dehydrogenase (LDH), creatinine, and ferritin, and prothrombin time (PT) were independent prognostic factors for 90-day OS from the diagnosis of HLH. Based on the above risk factors, the patients were further divided into two groups: low-risk (≤ 4 risk factors) and high-risk (> 4 risk factors), with overall 90-day survival rates of 82.7% and 28.1%, respectively (P<0.001). Conclusions: Patients with older age, coagulopathy, lower hemoglobin and AST levels, elevated LDH, creatinine and ferritin levels, and prolonged PT tended to have a worse prognosis. Moreover, our prognostic model provides the possibility of forecasting the clinical outcome of adult secondary HLH patients, although a larger sample, multicenter, randomized controlled clinical study is needed to verify the accuracy of the prognostic model.